Phytochemical analysis of the main groups of secondary metabolites in the Dracocephalum moldavica L. herb - M. I. Shanaida (The State Expert Center of the Ministry of Health of Ukraine, 2021)
The genus Dragonhead (Dracocephalum L.) includes 72 species of essential oil-bearing plants belonging to the Lamiaceae family. Many of them have long been used in a folk medicine of different countries. Moldavian dragonhead (D. moldavica L.) has been identified as the most promising species for the complex phytochemical research since it was successfully introduced in the climatic conditions of the Ukrainian forest-steppe zone and due to the presence of its various botanical forms and varieties.